Ações de qualidade de vida no trabalho: estudo de caso no Tribunal de Justiça do Estado da Bahia - ARAÚJO, Marina Laís de Araújo e (2015)
The purpose of this dissertation is to understand what are the limits and possibilities of implementation of actions and programs about Quality of Life at Work at the Tribunal de Justiça do Estado da Bahia. It is considered the Quality of Life at Work from the concept of Limongi-França (1996), as a set of shares of a company that involves the implementation of improvements and managerial, technological and structural innovations in the workplace.To achieve the goal, it conducted a case study of the Tribunal de Justiça do Estado da Bahia, from the use of a semi-structured interview with the Director of Human Resources and the application of a questionnaire with gazetted employees of the sticks located in Salvador Forums. Data were evaluated from the content analysis, descriptive and correlation. This is a qualitative and quantitative research, descriptive and exploratory. At the end of the study, it was observed that although there is a significant amount of actions implemented for the Quality of Life at Work and these shares represent a high level of compliance , there are more limits than possibilities to implement such actions. This fact is related to the context in which the body is inserted. In relation to the broader context is found, for example, the recent self-administration and spatial extent. As for the specific context it was found, for example, the lack of explanation as to the implementation and continuation of the realization of the actions and the fact that there is no amount allocated specifically for these actions. Thus, it appears that there is a lack of focus on the issue of treatment of Quality of Life at Work, and results as the low level of favorability concerning the actions implemented and the satisfaction of employees with their Quality of Life at Work. Thus, it is clear that even without systematization and planning, you can achieve results with the simple implementation of actions , however, these are important means to ensure that actions are properly implemented so that really fulfill their purposes, and also to identify other actions that may generate improvement in Quality of Life at Work.